Low-Avidity Antibodies to Carbonic Anhydrase-I and -II in Autoimmune Chronic Pancreatitise - Maria J. Bartolomé (The Scientific World Journal, 2002)
Antibodies (Abs) to carbonic anhydrase (isoforms CA-I and CA-II) have been considered pathogenic factors in the development of autoimmune pancreatitis. Besides, such autoAbs might accelerate the pancreatic damage in alcoholic chronic pancreatitis (CP). The aim of the present study was to evaluate the presence of serum Abs to CA-I and CA-II in CP and the relative affinity of these Abs.